دور سياسة الأجور في تحقيق الرضا الوظيفي دراسة حالة مؤسسة سونلغاز الأغواط - بلعمري أحلام; بقشيش هنية; شارف عبد القادر (جامعة عمار ثليجي الاغواط, 2022)
This study explains to us concept of wages and its most important objectives and the policy of the wages and its relationship to job satisfaction .Applied through a field study on wage policy and job satisfaction in the Electricity and Gas Distribution Corporation in